Molecular architecture of the PBP2–MreC core bacterial cell wall synthesis complex - Carlos Contreras-Martel (Nature Portfolio, 2017)
Bacterial wall biosynthesis is a complex process that requires the coordination of multiple enzymes. Here, the authors structurally characterize the PBP2:MreC complex involved in peptidoglycan elongation and cross-linking, and demonstrate that its disruption leads to loss of H. pylori shape and inability to sustain growth.